A Guide for Pain Management in Low and Middle Income Communities. Managing the Risk of Opioid Abuse in Patients with Cancer Pain - Joseph V Pergolizzi; Joseph V Pergolizzi; Joseph V Pergolizzi; Gianpietro eZampogna; Robert eTaylor; Edmundo eGonima; Jose ePosada; Robert B Raffa (Frontiers Media S.A., 2016)
Most patients who present with cancer have advanced disease and often suffer moderate to severe pain. Opioid therapy can be safe and effective for use in cancer patients with pain, but there are rightful concerns about inappropriate opioid use even in the cancer population. Since cancer patients live longer than ever before in history (and survivors may have long exposure times to opioid therapy), opioid misuse among cancer patients is an important topic worthy of deeper investigation. Cancer patients with pain must be evaluated for risk factors for potential opioid misuse and aberrant drug-taking behaviors assessed. A variety of validated screening tools should be used. Of particular importance is the fact that pain in cancer patients changes frequently, whether it is related to their underlying disease (progression or remission), pain related to treatment (such as painful chemotherapy-induced peripheral neuropathy), and concomitant pain unrelated to cancer (such as osteoarthritis, headache, or back pain). Fortunately, clinicians can use universal precautions to help reduce the risk of opioid misuse while still assuring that cancer patients get the pain therapy they need. Another important new tool in this regard is the emergence of abuse-deterrent opioid formulations.